Gender equality in international labor standars and fair recruitment - Pangol Lascano, Alberto (2023)
At the global level, the universalization of labor rights is in a stage of profound transformation, aimed at strengthening protective mechanisms. The States have committed to propose responses to all these challenges with multidimensional criteria and framed in the fulfillment of fundamental rights. This is how the ILO through the NIT includes principles and rights at work as enabling conditions that contribute to a better life condition of society. In this context, this research aims to analyze gender equality in international labor standards and fair hiring, through a legal-comparative analysis, responding to a qualitative research approach. The results made it possible to show that, although international labor standards have not been fully integrated into national legislation, which violates the principle of gender equality, since women continue to be discriminated against in terms of employment and occupation. In addition, globalization has affected the migration of workers, which is why the fair hiring process arises, promoted by the ILO, and whose initiative is to prevent abuses of workers, human trafficking and forced labor